Answer:
x² + (y – 3)² = 36
and
x²+ (y + 8)²= 36
Explanation:
The equation of circle that has a center (a, b) is given by the formula
(x - a)² + (x - b)² = r²
where r is the radius of the circle
If the circle lies on the y axis, its x-coordinate must be 0.
The radius of the circle = 1/2 x diameter = 1/2 x 12 = 6 units
So the equation must be of the form
(x - 0)² + (y - b)² = 36
We can eliminate x² + (y – 5)² = 6
We can also eliminate (x + 6)² + y² = 144
That leaves us with the two possible equations
x² + (y – 3)² = 36 (center at 0, 3)
and
x²+ (y + 8)²= 36 (center at (0, -8) )